Stock Valuation of PT Indika Energy Tbk: Impact of Net Zero Emission Transition - Mohammad Rusyad Salim; Sumirat, Erman Arif; Sukarno, Subiakto (Journal Integration of Social Studies and Business Development, 2023)
Climate change drives countries and the private sector to reduce their emission. Investors are becoming aware of sustainability issues and are more likely to prioritize companies demonstrating strong ESG. Adapting to this condition, coal mining companies in Indonesia are improving their ESG performance, one of which is PT Indika Energi Tbk (INDY). As one of the biggest mining companies in Indonesia, INDY has carried out sustainability initiatives and made it one of the companies with the best ESG scores compared to its competitors. However, Indika Energy's good ESG performance was not followed by its good stock performance. This phenomenon initiated the author to analyze how the business transition to low-carbon and Net Zero Emission (NZE) development by INDY will affect the stock valuation. The valuation was based on the Discounted Cash Flow (DCF) method, forecasting ten years of future financial statements considering the company's past performance and strategy. The evaluation was conducted under the Business-As-Usual (BAU) and the NZE Transition Scenario. The author also calculates relative valuations to achieve a more thorough and robust assessment of company value. Based on the DCF method, the intrinsic value of INDY is Rp 2,899 and Rp 2,726 per share for BAU and the NZE Transition Scenario, respectively, while the market price of a share is 1,910 as of the end of Jun-23, which indicated that current share price is undervalued. Therefore, it is recommended that investors buy INDY stock at the current price. The results also showed that the company's diversification strategy did not increase the value of its shares. This outcome might be attributed to the lack of strong incentives from the government or the capital market for supporting sustainable business practices. The company should take the initiative to increase the value, optimize capital structure, and assess assets.